2017
DOI: 10.21307/jofnem-2017-078
|View full text |Cite
|
Sign up to set email alerts
|

Superparasitism and Population Regulation of the Mosquito-Parasitic Mermithid Nematodes Romanomermis iyengari and Strelkovimermis spiculatus

Abstract: Superparasitism is a common phenomenon in mosquito-parasitic mermithid nematodes. Multiple nematodes are needed in a single host to produce males. Host selection behavior and intraspecific competition among Romanomermis iyengari and Strelkovimermis spiculatus were investigated against their host, Culex pipiens pipiens in laboratory experiments. In a choice assay between previously infected and uninfected host larvae, infectious preparasites of both nematode species could distinguish not only between infected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…To decrease mortality during development, females tend to lay more male offspring in larger clutch sizes, which is a maternal strategy to ensure male offspring survival and avoid zero fitness in female offspring (Green et al, 1982; Hardy & Cook, 1995). Mortality during development may be caused by self‐superparasitism in some species (Narayanan & Rao, 1955; Jackson, 1961; Rotary & Gerling, 1973; Devescovi et al, 2017; Sanad et al, 2017; Duval et al, 2018). Male survival is better than females (Ueno & Tanaka, 1997) under low‐egg quality conditions at the end of oviposition.…”
Section: Discussionmentioning
confidence: 99%
“…To decrease mortality during development, females tend to lay more male offspring in larger clutch sizes, which is a maternal strategy to ensure male offspring survival and avoid zero fitness in female offspring (Green et al, 1982; Hardy & Cook, 1995). Mortality during development may be caused by self‐superparasitism in some species (Narayanan & Rao, 1955; Jackson, 1961; Rotary & Gerling, 1973; Devescovi et al, 2017; Sanad et al, 2017; Duval et al, 2018). Male survival is better than females (Ueno & Tanaka, 1997) under low‐egg quality conditions at the end of oviposition.…”
Section: Discussionmentioning
confidence: 99%
“…These nematodes are highlighted as potential vector biocontrol candidates, due to their parasitic relationship with various arthropods and several arachnids ( Stabler, 1952 ; Chapman, 1974 ). The hatched pre-parasitic juveniles of mermithid nematodes aggressively infect mosquito larvae (usually the early instars) by paralyzing the targeted hosts, followed by penetration of cuticular wound to establish the infection ( Sanad et al, 2017 ). Once infected, the mermithid parasites take over the cellular function regulatory authority of their hosts.…”
Section: Pathogenesis-mediated Vector Biocontrolmentioning
confidence: 99%
“…The emerged post-parasite stage then molts into the free-living adult to reproduce and lay eggs. Multiple mermithids may repeatedly infect an already infected larva, giving rise to a phenomenon called superparasitism ( Sanad et al, 2017 ). Different research groups have demonstrated the mosquito larvicidal effect of several mermithids such as Romanonermis iyengari (against Ae.…”
Section: Pathogenesis-mediated Vector Biocontrolmentioning
confidence: 99%
See 1 more Smart Citation
“…The larvicidal toxins produced by Bti and Lysinibacillus sphaericus ( Ls ) have been used in biological control since their discovery and have been extensively commercialized. Penetration of mermithid nematodes, especially Romanomermis species, in mosquito larvae has also been evaluated for the development of biological control strategies [48]. However, it has proven difficult to commercialize because the viability of the microorganisms is difficult to maintain in storage and transportation.…”
Section: Application Of Microorganisms To Mosquito Controlmentioning
confidence: 99%